Aktivitas Sukuk Ijarah Rasulullah, Masa Khulafa Ar-Rasyidin Masa Dinasti Umayyah pada Masa Dinasti Abbasiyyah - Ma, Maryam Batubara; Fatahillah, Lou; Sari, Novita; Siregar, Jumriani; Harahap, Siska Permata Sari (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Sukuk is a long-term security based on sharia issued by the issuer to sharia loan holders, which requires the issuer to pay the sharia loan holder's income in the form of profit sharing/margin/premium and repayment of interest funds at maturity. This statement is the definition of sharia bonds according to the National Sharia Council (DSN) No.32/DSNMUI/IX/2002. In Indonesia, according to the fatwa issued by the National Sharia Council, one of the types of sukuk is ijárah sukuk. Ijárah sukuk is financing that uses the ijárah contract system, or securities containing financial contracts based on sharia principles, which are issued by the issuing corporation, government or other institutions which require the sukuk issuer to pay a certain amount of compensation to the sukuk owner.rent out property and pay off family fixed assets on time. There are three parties involved in the sukuk ijárah contract. These contracts are investment contracts, namely between investors (sukuk holders) and special purpose vehicles (SPV) or collective investment contracts, sale and purchase contracts between SPV/KIK and suppliers or sellers of assets (goods), and lease contracts (ijárah) or sale and purchase contract. purchase between SPV/KIK and company or property tenants. Issuing sukuk in the capital market requires preparation for sukuk issuance.